Last night in Brooklyn : a novel - Gonzalez, Xochitl, 1977- (Flatiron Books, 2026)
"New York Times bestselling author Xochitl Gonzalez delivers a captivating story about a young woman whose life becomes ensnared in her glamorous neighbor's secret past, laying bare the mounting tensions at play in a rapidly gentrifying, early 2000's Fort Greene, Brooklyn. SPRING, 2007 At twenty-six, Alicia Canales Forten feels smothered by her future. She's in a long-distance relationship, living at home with her mother's beliefs, saving up for her wedding to a future doctor. But after Alicia ventures out one night in the neighborhood of Fort Greene, Brooklyn, she finds herself lured by the siren song of youth and possibility that the striving crowd of creatives holds, and moves in. No one embodies this more than La Garza, a larger-than-life, up-and-coming fashion designer whose epic house parties fuel neighborhood lore. La Garza's life, observed by Alicia from her apartment across the street, seems to hold the allure and fearlessness Alicia has never dared to imagine for herself. But when Alicia's wealthy banker cousin moves to the neighborhood, she finds herself increasingly drawn into both his and La Garza's precarious lives. Against the backdrop of a potentially life-changing presidential election and a looming once-in-a-generation fiscal crisis, Last Night in Brooklyn explores the dark compromise of the American Dream for people of color living, unknowingly, in the twilight of a cultural moment. It is a story about everything money can buy--and the destruction of what it can't"--